Jessica's mermaid - Stewart, Molly Mia; Pascal, Francine Hu, Ying-Hwa (Bantam Books New York, 1994)
Jessica has been "crying wolf" and her friends are getting tired of it. So when she says that she has seen a mermaid no one believes her. But, this time Jessica isn't kidding. Now she must find the mermaid- or she may lose all her friends